Analysis Of The Implementation Of The Principles Of Good Corporate Governance On Public Perception And Financial Performance At The Regional Drinking Water Company (PDAM) Of Palopo City - Afdal Kurniawan Jamaludin; Agus Abdul Aziz; Arwin Yafi Rahmatullah; Dimas Aprilian; M. Sandi Surya Erlangga (International Journal of Sociology of Religion, 2023)
Good Corporate Governance (GCG) is a company's effort to create a conducive relationship between stakeholders, so that it becomes more focused and clearer in the division of duties, responsibilities and supervision. Good Corporate Governance (GCG) has an impact on company performance. Company performance is the value generated by the company in a certain period with reference to certain standards. Good company performance is seen in the company's financial performance. Corporate Financial Performance is also called a determination that measures the good and bad of the company in work performance and can be seen from its financial condition in a certain period. The method used in this research is a balanced qualitative and quantitative mixed approach (Concurrent Triangulation), using a case study approach. The sampling technique used purposive sampling and the number of samples of this study were 36 PDAM employees and 50 people. The results showed that the implementation of the principles of Good Corporate Governance (GCG) at PDAM palopo city is very good, public perception of PDAM palopo city is good, Financial Performance at PDAM palopo city from 2010-2014 has decreased significantly in terms of profitability, and Good Corporate Governance (GCG) has a low positive relationship before the implementation of the principles of Good Corporate Governance (GCG). and after the implementation of Good Corporate Governance (GCG).